Climate justice and human development: A systematic literature review - Furlan Matos Alves, Marcelo Wilson; Mariano, Enzo Barberio [UNESP] (Elsevier B.V., 2018)
The objective of this paper is to carry out a systematic review of the literature on climate justice from the point of view of the capabilities approach. This review had as object of study 53 papers selected in the Web of Science and Scopus databases, and focused on the following dimensions: starting models for the preparation of action plans (Basic Rights, Polluter Pays, and Fair Division), types of actions adopted (adaptation and mitigation), level of adoption (macro and micro) and individual freedoms affected (economic, political, social, transparency guarantees and protective security). The main results and contributions of the study are: a) the Basic Rights model is more frequently used than the other two; b) there is a prevalence of some freedoms when analysed in the context of adaptation and mitigation actions; c) opportunity to apply quantitative methods and mixed methods on climate justice analysis; d) a theoretical framework organization of the concepts related to the link between climate justice and human development, which can help future research on the subject as well as contribute to the cooperation among academics and policy makers post-Paris Agreement. (C) 2018 Elsevier Ltd. All rights reserved.